Corporate Social Responsibility and Organizational Psychology: Quid pro Quo - Ante Glavas (Frontiers Research Topics, 2017)
Researchers, corporate leaders, and other stakeholders have shown increasing interest in Corporate Social Responsibility (CSR)-a company's discretionary actions and policies that appear to advance societal well-being beyond its immediate financial interests and legal requirements. Spanning decades of research activity, the scholarly literature on CSR has been dominated by meso- and macro-level perspectives, such as studies within corporate strategy that examine relationships between firm-level indicators of social/environmental performance and corporate financial performance. In recent years, however, there has been an explosion of micro-oriented CSR research conducted at the individual-level of analysis, especially with respect to studies on how and why job seekers and employees perceive and react to CSR practices. This micro-level focus is reflected in 12 articles published in this edited volume as a research topic collection in Frontiers in Psychology (Organizational Psychology Specialty Section) titled "Corporate social responsibility and organizational psychology: Quid pro quo."